The dynamics of deciduous dipterocarp forest in relation to climate variability in the Sakaerat Biosphere Reserve, Northeastern Thailand - CHATPIMUK YATAR; SATHID THINKAMPHEANG; SARAWOOD SUNGKAEW; CHONGRAK WACHRINRAT; LAMTHAI ASANOK; TORLARP KAMYO; SUTHEERA HERMHUK; PANIDA KACHINA; JAKKAPONG THONGSAWI; WONGSATORN PHUMPHUANG; ARERUT YARNVUDHI; SURACHIT WAENGSOTHORN; SOMBOON CHEYSAWAT; DOKRAK MAROD (Society for Indonesian Biodiversity, 2024)
Abstract. Yatar C, Thinkampheang S, Sungkaew S, Wachrinrat C, Asanok L, Kamyo T, Hermhuk S, Kachina P, Thongsawi J, Phumphuang W, Yarnvudhi A, Waengsothorn S, Cheysawat S, Marod D. 2024. The dynamics of deciduous dipterocarp forest in relation to climate variability in the Sakaerat Biosphere Reserve, Northeastern Thailand. Biodiversitas 25: 3088-3098. Climate change is a major environmental problem influencing forest dynamics. To clarify tropical seasonal forest dynamics under climate change, we conducted long-term monitoring of all trees with Diameter at Breast Height (DBH) ?4.5 cm within a 1-ha permanent plot established in 2004 in a deciduous dipterocarp forest in the Sakaerat Biosphere Reserve (SBR), Northeastern Thailand. Surveys of all trees within the plot with DBH ?2 cm were conducted in 2008, 2015, and 2019. Climate data were obtained from the SBR climate station during 2004-2019 and used to extract dates with drought and wet conditions. Forest dynamics varied among species and periods, with stem density exhibiting a decreasing trend. Despite prolonged drought conditions from 2004 to 2009, which usually leads to increased mortality rates, the recruitment rate was 7-fold higher than the mortality rate at a site protected from fire during 2004-2008, and most of the recruited species were pioneer species, shrubs, and small trees. A contrasting trend was observed during 2015-2019, with a mortality rate almost 10-fold higher than the recruitment rate, indicating a significant ecological disturbance, likely to have been driven by a severe El Niño event during 2015-2016. Thus, climate induced disturbances (i.e., drought and fire) appear to have inhibited tree regeneration in the deciduous dipterocarp forest, particularly when they occurred in combination and for specific timing and intensity levels. Addressing the challenges posed by drought and fire to tree regeneration requires holistic management approaches that consider both ecological and climatic factors. Monitoring and adaptive management are also essential to mitigate the impact of future disturbances and support the long-term viability of forest ecosystems.